Financing American Higher Education: Reviewing the Trend in Student’s Perceptions of Their Student Debt - Mbah, Ruth Endam (Advances in Social Sciences Research Journal, 2023)
This paper reviews existing pieces of literature on student debt, specifically perceptions of student debt and debt repayment strategies in the USA. The policy decision to shift from need-based grants as a means of financing college education to student loans in the 1990s changed the trajectory of higher education, especially for low-income families. Most American college students now have to rely significantly on student loan debt to finance higher education, especially among those who see these loans as an investment. While in school, most college students seem to be unrealistically optimistic about paying their debt upon graduation, which may be an explanation for the huge debt delinquency rate we record in the US. Many graduate colleges today with an unbearable outstanding amount of student loan debt. This explains the consistent correlation between student debt and financial anxiety or stress reported in most studies as student debt and credit card debt have become a significant part of the American college student. There is, therefore, a need for the incorporation of accurate financial literacy programs in our curriculums starting from high school.